An examination of effectiveness of technology push strategies for achieving sustainable development in manufacturing industries. Issue 1 (28th February 2018) - Singla, Anuj; Ahuja, Inderpreet Singh; Sethi, Amanpreet Singh
Abstract : Purpose: The purpose of this study is to estimate and extract various significant technology push (TP) strategies influencing sustainable development in Indian manufacturing industries. The study critically examines the effectiveness of TP strategies in manufacturing enterprises. Design/methodology/approach: An extensive survey of 92 companies has been executed to identify improvements made by TP strategies to achieve sustainable development in manufacturing industries. The companies in the survey include medium− and large−scale manufacturing enterprises. The correlations between various TP strategies and sustainable development indicators are evaluated and validated using various numerical methods and tools. Findings: The focus of the paper is on the distinguishable contributions made by TP strategies such as innovative capability; research and development; corporate strategy; and export orientation toward achieving sustainable development. The inter−relationships between different TP practices with sustainable development indicators have been evaluated to efficiently manage the objectives of growth and sustainability. The research concludes that two TP strategies, namely, corporate strategy and innovative capability, are found to be substantial in the present context. These strategies have emerged as a foundation for several development initiatives and actively support manufacturing industries in accomplishing sustainable development. however, enterprises need to work more actively on improving less significant issues of TP. Research limitations/implications: In the present investigation, contributions made by TP practices have been evaluated to accomplish sustainable development in Indian manufacturing industries. Hence, the results obtained may need some modifications before applying to other countries. Moreover, issue−wise independent modeling can also be performed to assess the importance of TP strategies under specific orientations. Practical implications: The research gives priority to enhancement in the planning among various TP practices and sustainable development indicators in the industries to impart TP as an important practice to meet various challenges of competent markets worldwide. Social implications: It has been exhibited from the observations that adequate TP strategies can efficiently contribute toward recognition of sustainable development to compete in the highly progressive global market. The results of various inter−relationships among TP practices and sustainable development indicators represent the effectiveness of TP practices for accomplishment of social and organizational objectives. Originality/value: It has been investigated in the present study that TP practices are significant initiatives taken by the manufacturing industries for performance improvement and sustainable development. The paper elaborates the study to find out TP issues that need to be assessed significantly to avail the advantages of sustainable development and to meet the challenges posed by global market. The inter−relationships among TP strategies and sustainable development indicators have been analyzed using various statistical tools and techniques, such as inter−item covariance test; Pearson's correlation analysis; multiple regression analysis; analytic hierarchy process and canonical correlation analysis.